2016
DOI: 10.2174/1567205013666160401115307
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoprotein E (ApoE) Polymorphism with Alzheimer';s Disease in Chinese Population

Abstract: Apolipoprotein E (ApoE) plays a vital role in cholesterol metabolism and its allele polymorphisms have been associated with several diseases including Alzheimer's disease (AD). There are few systematic studies on ApoE polymorphism and its association with AD in Chinese population. To examine this issue, participants included 4251 subjects and 404 AD patients with 390 healthy elderly residing in Chongqing city were genotyped. The results showed that the ε3 allele presented the highest frequency (82%), followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The APOE gene polymorphism is associated with the risk of developing many central nervous system disorders. APOE polymorphism has been recognized as a genetic risk factor for the development of Alzheimer's disease in different populations ( Achouri-Rassas et al, 2015 , Kumar et al, 2015 , Zheng et al, 2016 ). In Chinese population, APOE polymorphism is associated with the risk of developing deep venous thrombosis ( Zhu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The APOE gene polymorphism is associated with the risk of developing many central nervous system disorders. APOE polymorphism has been recognized as a genetic risk factor for the development of Alzheimer's disease in different populations ( Achouri-Rassas et al, 2015 , Kumar et al, 2015 , Zheng et al, 2016 ). In Chinese population, APOE polymorphism is associated with the risk of developing deep venous thrombosis ( Zhu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 11,884 twins has shown that genetic predisposition accounts for 58-79% of Alzheimer's disease cases (Gatz et al, 2006). Previous studies have indicated that genetic polymorphisms in protein tyrosine kinase 2b, presenilin 2, apolipoprotein E, cytochrome 46A1, disrupted-in-schizophrenia-1, 3-hydroxy-3-methylglutaryl-CoA reductase, and sortilin receptor 1 all play essential roles in the development of this disease (Chang et al, 2016;Huang et al, 2016;Jia et al, 2016;Li et al, 2016;Suzuki et al, 2016;Zhang et al, 2016;Zheng et al, 2016). Previous studies have reported that alcohol consumption is associated with risk of Alzheimer's disease (Piazza-Gardner et al, 2013;Berntsen et al, 2015;Ilomaki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…APOE is a well-known apolipoprotein that functions in lipoprotein-mediated lipid transport between organs via the plasma and interstitial fluids (44). As a secreted protein, APOE has been implicated in lipoprotein metabolism and the pathogenesis of Alzheimer's disease and atherosclerosis (45)(46)(47). However, its association with tumors has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%